Fiber Polypropylene Dalam Campuran Beton dan Mortar Semen - F.Eddy Poerwodihardjo; Dwi Istiningsih (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2016)
The use of fiber Polypropylene in Mixed Concrete and Cement Mortar for buildings has been widely recommended, to improve the performance of tensile strength and flexural strength of concrete and cement mortar so as to increase the strength of the structure against earthquake forces.Polypropylene fibers are available in two forms namely monofilament (spinning) and fiber movies. Properties of polypropylene fibers has a regular arrangement of atoms in the molecule polymer with a high crystallisation called Isotactic Polypropylene, with a melting point of 165 0C, is Hidrophobic / not-wet cement paste and do not absorb water. Mixing of fibers in fresh concrete and mortar mixing cement made at the time before the mixing process ends. Mixer fibers will scatter evenly on the concrete / cement mortar so that the process of casting / molding and compaction to the structural elements can be done easily, either structural elements thick and thin structure elements. This is evident from the results Slump test or V-B test on Fas 0.5 by 5-10 cm. The nature of hard concrete and cement mortar mixed with polypropylene fibers have good strong belt, the number of cracked slightly and lower heat of hydration. From the results of various tests increased tensile strength and flexural strength and resistance to impact crushed concrete also increased, better fire resistance to concrete and cement mortar has a level of durability / high durability. From the results of the stress and strain curves show, at a maximum voltage of 20 MN / m2 occur fairly large strain after cracking but the stress declined sharply not so strong polypropylene fiber concrete buttress structural loads that occur. Keywords: fiber-reinforced concrete, tensile strength, durable. ABSTRAKPenggunaan fiber Polypropylene dalam Campuran Beton dan Mortar Semen untuk bangunan gedung sudah banyak direkomendasikan, untuk meningkatkan kinerja kuat tarik ,kuat lentur beton dan mortar semen sehingga dapat menambah kekuatan struktur terhadap gaya gempa. Serat polypropylene tersedia dalam dua bentuk yaitu monofilament( pintal ) dan serat film. Sifat serat polypropylene memiliki susunan atom biasa dalam molekul polymer dengan kristalisasi tinggi yang disebut Isotactic Polypropylene, dengan titik leleh 165 0C , bersifat Hidrophobic/ tidak basah terkena pasta semen dan tidak menyerap air. Pencampuran serat pada adukan beton segar maupun mortar semen dilakukan pada saat sebelum proses pencampuran berakhir. Pengaduk akan menghamburkan serat secara merata pada adukan beton/mortar semen sehingga proses pengecoran/pencetakan dan pemadatan pada elemen struktur dapat dilakukan dengan mudah, baik elemen struktur yang tebal maupun elemen struktur yang tipis. Hal ini terlihat dari hasil Slump test atau V-B test pada Fas 0,5 sebesar 5 – 10 cm. Sifat beton keras dan mortar semen yang dicampur serat polypropylene memiliki kuat ikat yang baik, jumlah retak sedikit dan panas hidrasi rendah. Dari hasil berbagai pengujian kekuatan tarik dan lentur meningkat, kekuatan terhadap benturan dan ketahanan hancur beton juga meningkat, ketahanan terhadap api lebih baik sehingga beton dan mortar semen memiliki tingkat durabilitas/keawetan yang tinggi. Dari hasil kurva tegangan dan regangan menunjukkan, pada tegangan maksimal 20 MN/m2 terjadi regangan yang cukup besar setelah terjadi retak tetapi tegangan tidak menurun tajam sehingga beton serat polypropylene kuat menopang beban struktur yang terjadi.Kata kunci : beton serat,kuat tarik,awet.